Hygienic and sexual habits of womem with recurrent vulvovaginitis - Cordeiro, Sílvia N.; Turato, Egberto R.; Viceníini, Regina Maria R.; Gonçalves, Ana Katherine S.; Giraldo, Paulo César (Brazilian Journal of Sexually Transmitted Diseases, 2003)
[...]